Does aid for education attract foreign investors? An empirical analysis for Latin America - Julian Donaubauer; Dierk Herzer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2012)
We address the question of whether foreign aid helps attract foreign direct investment (FDI). This could be achieved if well targeted aid removed critical impediments to higher FDI inflows. In particular, test the hypothesis that aid for education is an effective means to increase FDI flows to host countries in Latin America where schooling and education appears to be inadequate from the viewpoint of foreign investors. We employ panel data techniques covering 21 Latin American countries over the period from 1984 to 2008. We find that aid for education has a statistically significant positive effect on FDI. This effect is robust to potential outliers, sample selection, alternative specifications and different estimation methods.
Keywords: E24; F21; F35; O15; O19; 330; foreign aid; foreign direct investment; aid effectiveness; human capital